1989
DOI: 10.1115/1.3188754
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Experimental Analysis of Acoustic Emission from Metal Cutting

Abstract: Testing parameters characterizing acoustic emission (AE) detected during metal cutting may be theoretically correlated, in a simple manner, to work material properites, cutting conditions, and tool geometry. Experimental results, obtained during turning by different researchers using different AE techniques, are presented and critically assessed with reference to their reciprocal agreement as well as their agreement with theoretical predictions. A review of current methods for AE analysis is also presented and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1
11

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 11 publications
0
10
1
11
Order By: Relevance
“…The square of the RMS value is directly proportional to the energy released during an AE event (Table 1). Results [11,15] indicate that the AE energy is little affected by changes on feed rate and depth of cut (and hence volume of plastic deformation), contrary to the prediction of the theoretical models. The power spectrums of AE signals obtained in this research generally confirmed this observation.…”
Section: Effect Of Cutting Conditions On Acoustic Emissioncontrasting
confidence: 42%
See 2 more Smart Citations
“…The square of the RMS value is directly proportional to the energy released during an AE event (Table 1). Results [11,15] indicate that the AE energy is little affected by changes on feed rate and depth of cut (and hence volume of plastic deformation), contrary to the prediction of the theoretical models. The power spectrums of AE signals obtained in this research generally confirmed this observation.…”
Section: Effect Of Cutting Conditions On Acoustic Emissioncontrasting
confidence: 42%
“…The following relationship between the emission signal and its source was obtained. The AE total count, which is the number of times the signal overcomes a threshold voltage, has been correlated in a simple manner to the energy of the signals reaching the transducer [15] (and hence the energy of the signals generated by the AE source). Table 1 shows a summary of the findings.…”
Section: Theoretical Relationships Between Acoustic Emission and Metamentioning
confidence: 99%
See 1 more Smart Citation
“…In manufacturing research, success has been achieved using acoustical signals from machining and forming operations (see [3], [13], and [16]). In work involving punch stretching and deep drawing of aluminum sheet metal, an acoustical sensor was placed in direct contact with the sheet metal during the forming process [7].…”
mentioning
confidence: 99%
“…These elastic waves can be detected by transducers attached to the surface of the specimen. Research into the use of acoustic emission for tool wear monitoring [15][16][17][18][19] has established that there exists a definite relation between AErms and tool wear.…”
Section: A Acoustic Emission and Tool Wearmentioning
confidence: 99%